Notice of Meeting of the Aviation Advisory Commission May 3, 2001 (2001)
The agenda for a meeting on May 3, 2001 of the Aviation Advisory Commission. Discusses the budget for 2001-2002 and the Department of Airports' Rent and Fee Schedule.